2010
DOI: 10.1021/jo1015882
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Regioselectivity in Nucleophilic Photosubstitution of 4-Nitroanisole. The Activation Energy Criterion for Regioselectivity

Abstract: Photosubstitution of the nitro group vs the methoxy group of triplet 4-nitroanisole by hydroxide ion in water leads to product yields of about 80% 4-methoxyphenol and 20% 4-nitrophenol. The ratio depends slightly on temperature from 3 to 73 °C. The slight temperature variation in the yield ratio is reproduced almost perfectly with a simple Arrhenius model for a mechanism involving bonding of hydroxide ion with the triplet state of 4-nitroanisole. The competing transition states have activation energies of 2.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The approach was extended to an electron transfer/geminate radical recombination mechanism (S N (ET) Ar*) of photosubstitution, first for intramolecular photosubstitutions (photo-Smiles rearrangements) and then for intermolecular reactions . These reactions were said to be LUMO-controlled, in contrast to the S N 2 Ar* type that were HOMO-controlled. , We , and others have criticized this model. It rests on the assumption that the ground state frontier orbitals (HOMO and LUMO) persist in the reactive excited state, even if it is a triplet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach was extended to an electron transfer/geminate radical recombination mechanism (S N (ET) Ar*) of photosubstitution, first for intramolecular photosubstitutions (photo-Smiles rearrangements) and then for intermolecular reactions . These reactions were said to be LUMO-controlled, in contrast to the S N 2 Ar* type that were HOMO-controlled. , We , and others have criticized this model. It rests on the assumption that the ground state frontier orbitals (HOMO and LUMO) persist in the reactive excited state, even if it is a triplet.…”
Section: Discussionmentioning
confidence: 99%
“…This seems a significant oversight. We know of no experimental study, other than our recent one, 10 showing that photochemical regioselectivity depends on relative activation energies or even that the primary criterion for a proxy method should be its representation of activation energy. Our report 10 concerned a reaction that gave two substitution photoproducts.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The aqueous photolysis of oxyfluorfen produced the corresponding phenol derivative as one of the main products. 4,154) Although DFT calculations suggested that the triplet process via σ-complex formed by attacking OH − at the nitro-bearing carbon was favorable in the photo-induced hydrolysis of 4-nitroanisole, 155) the quenching study in the photolysis of oxyfluorfen showed the involvement of neither excited triplet states nor radicals; therefore, the mechanism is still unclear. 156) A similar photosubstitution is also known for parathion-methyl 157) and the benzoic acid photoproduct of mesotrione.…”
Section: )mentioning
confidence: 99%
“…Although standard methodologies do make use of natural organic matter, which behaves as a triplet sensitizer to induce photolysis, and pH for molecules readily ionized under environmental conditions, they do not account for ionic strength. The pH of the solution could exhibit effects on molecules susceptible to nucleophilic substitution, which do not have sufficiently appreciable pKa values to warrant pH adjustments, such as nitro aromatics [16][17][18]. The photolytic rate for TNT has also been shown to be directly correlated with ionic strength [19].…”
Section: Introductionmentioning
confidence: 99%